Multiple cross-linking induced lignin-based liquid mulch film for soil stabilization and crop growth promotion - Tayeh, Cristina; Kannan, Paulo; Rudy, Riatee (Journal of Green Energy and Environmental Engineering, 2023)
In response to the white pollution and microplastic risks caused by the widely used PE film in arid and semi-arid regions of China, this study, guided by the goal of enhancing the utilization value of biomass resources, proposes a new strategy for preparing liquid film based on non-covalent bonding self-assembly. The aim is to develop green biobased covering materials and provide a PE film replacement solution for the conservation of cultivated land in arid and semi-arid areas. Using lignosulfonate sodium, chitosan and polyvinyl alcohol as raw materials, a ternary composite sprayable multi-crosslinked induced lignin-based liquid film (LCP) was prepared by adjusting the mass ratio of chitosan and polyvinyl alcohol. Fourier transform infrared spectroscopy, isothermal drop quantitative calorimetry and rotational rheology were used to characterize the physicochemical structure of LCP; the mechanical properties were tested using a universal testing machine, and the optimal ratio and spraying amount of LCP were determined by evaluating water vapor permeability, crop growth characteristics and soil retention capacity. The synthesis of LCP is mainly driven by hydrogen bonding and electrostatic interaction, and it has significant shear thinning characteristics. When the ratio of LS:CS:PVA (mass ratio of lignosulfonate sodium, chitosan and polyvinyl alcohol) is 10:4:4, the prepared LCP has the best performance, with a mechanical strength of 24.05 MPa, a water vapor permeability of 352.10 g/(m²·d), a seed germination rate of 95%, and an average root length of 19.44 mm. Compared with the untreated treatment, when the dry matter spraying amount is 8 g/m², the crop emergence rate, plant height and total biomass are significantly increased by 45.45%, 26.90% and 54.99%, respectively, and the soil retention effect is also significantly enhanced. The liquid mulch film prepared in this study can effectively promote crop growth and enhance soil retention capacity, providing important references for the reduction of PE film usage and the high-value utilization of agricultural and forestry wastes, and has broad application prospects.